The new variable-length key symmetric cryptosystem - Pour, Davood Rezaei; Md. Said, Mohamad Rushdan; Mohd Atan, Kamel Ariffin; Othman, Mohamed (Science Publications, 2009)
Problem statement: In this study, we proposed a new 64-bit block cipher that accepted a variable-length key up to 512 bits, which was suitable for implementation in a variety of environments.